Distinction of Societal Religiosity During Covid-19 Pandemic Era - Umi Hanik; A Zahid (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2021)
This research is a historical reflection of the condition of the Indonesian people who were battered by the Covid-19 pandemic, not only in the economic, political, social, and even psychological sensations of the people in doing religious activities. The interests overlap with the dedication on behalf of the community, from the self-quarantine system, large-scale social restrictions (PSBB), and, no doubt, the public who are less aware of the existence of Covid-19, resulting in the increased statistical number of Covid-19 confirmed cases.It hasbeen a year that the Indonesian people have been plagued by this never ending problem, and like a spotlight, Covid-19 always looms over people’s lives. The people’s attitudes vary, starting from the assumption that Covid-19 is God's army to finish off arrogant humans, to Covid-19 as a scientific reality proven through empirical research. The perspective dualism of the Indonesian people is interesting to discuss in the form of societal religiosity sensations, both of which have a deep distinction in the context of the COVID-19 pandemic. Even if the religious community really understands the religion (Islam) in a deep way, of course, it is very clear how to respond to Covid-19 in the style of Prophet Muhammad SAW and the history of the companions of the Prophet.